Determination of hot-electron drift velocity in (Be)ZnMgO/ZnO 2DEG channels. (1st January 2023) - Ardaravičius, Linas; Kiprijanovič, Oleg; Šermukšnis, Emilis; Avrutin, Vitaliy; Özgür, Ümit; Morkoç, Hadis
Abstract: Recent experimental study of electron transport in ZnO/ZnMgO and BeZnMgO/ZnO heterostructures containing two-dimensional electron gas (2DEG) channels of two polarities is reported where electrons are accelerated and become hot by a pulsed electric field. The measurements with electrical pulses ranging from 2 ns to 10 ns in duration ensure the control of self-heating effect. Electron transport in the ZnO 2DEG channels located in ZnO layers at the ZnMgO or BeZnMgO barrier or in ZnO 3DEG channels is treated mainly in terms of drift velocity. The highest values of 1.3 × 10 7 cm/s at 360 kV/cm, 2.0 × 10 7 cm/s at 270 kV/cm, and 2.5 × 10 7 cm/s and 320 kV/cm, respectively, are attained and explained by emphasizing the effect of hot phonons.